2015
DOI: 10.1080/09205063.2015.1065597
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterisation of a modifiable soft macro-porous hyaluronic acid cryogel platform

Abstract: A facile method for the synthesis of cell supportive, highly macro-porous hyaluronic acid (HA) hydrogels via cryogelation is presented. Unmodified HA was chemically cross-linked via EDC/NHS zero-length cross-linking at sub-zero temperatures to yield cryogels with high porosity and high pore interconnectivity. The physical properties of the HA cryogels including porosity, average pore size, elasticity and swelling properties were characterised as a function of cryogelation conditions and composition of the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In particular, increasing the amount of EDC had a much greater impact on scaffold stiffness and made it possible to mimic healthy or cirrhotic mechanical properties. Henderson et al observed the same trends with hyaluronic acid cryogels cross-linked with EDC by varying the Y from 1 to 10 kPa [56]. To obtain a Y corresponding to intermediate fibrosis states, other AAD:EDC ratios should be tested, rather than increasing the alginate concentration over 2% because of high viscosity solution.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, increasing the amount of EDC had a much greater impact on scaffold stiffness and made it possible to mimic healthy or cirrhotic mechanical properties. Henderson et al observed the same trends with hyaluronic acid cryogels cross-linked with EDC by varying the Y from 1 to 10 kPa [56]. To obtain a Y corresponding to intermediate fibrosis states, other AAD:EDC ratios should be tested, rather than increasing the alginate concentration over 2% because of high viscosity solution.…”
Section: Discussionmentioning
confidence: 81%
“…54 For example, multiple bioreactors could be assembled in series or in parallel, similar to the concept of using multiple, continuously perfused microchambers in microfluidic devices to create "organs-on-chips". 55,56 The tissue engineering scaffolds used here can support cell cultures, 35 and we have performed initial tests using 3D cell cultures inside the bioreactors. Although this introduces additional complexity (sterile conditions and incubation required) this could enable new types of bio-nano and particle-scaffold interactions to be investigated under physiologically relevant flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins cryogels (tissue engineering scaffolds described previously), 35,36 connect the bioreactors in-line to the circulation system, inject particles into the circulation, and study the particle interactions with the gels using flow cytometry and confocal laser scanning microscopy. We study and compare two types of soft polymer particlespoly(ethylene glycol) (PEG) and poly(methacrylic acid) (PMA) based particles-and show that material-dependent interactions affect particle removal from circulation in both the gel and scaffold systems.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffolds were left to incubate for 2 hours to allow cell attachment to the scaffold, following which a further 150 µl of DMEM was added to each well. This facilitates cell penetration and attachment in the scaffolds using capillary action to carry the suspension into the scaffold as it swells (51). Scaffolds loaded with cells were incubated for 3 days with the culture media being changed every 24 hours.…”
Section: Fibroblast Culture On Scaffoldsmentioning
confidence: 99%